The technique for less infectious and earlier healing of stoma closure wound: negative pressure wound therapy with instillation and dwelling followed by primary closure - Yane, Yoshinori (BMC Surg, 2021)
BACKGROUND: Temporary stomas have been widely used to avoid the risk of complications such as anastomotic leakage after colorectal resection. Stoma closure is relatively easy; however, postoperative surgical site infection (SSI) may be a problem. Various methods have been used to reduce the incidence of SSI. We aimed to evaluate a new technique for stoma wound closure. METHODS: We enrolled patients who underwent stoma closure at our hospital between September 2019 and May 2020. We selected patients who lived far from our hospital and had difficulty visiting the hospital regularly and who agreed to undergo this surgical technique. We used negative pressure wound therapy with instillation and dwelling (NPWTi-d) and delayed primary closure for these patients. RESULTS: Four patients underwent NPWTi-d and delayed primary closure without the occurrence of SSI. The median postoperative hospital stay was 9 days (range: 7–14 days), and the median number of days to confirmation of epithelialization was 11.5 days (range: 10–16 days). CONCLUSION: The combined use of NPWTi-d and delayed primary closure for the stoma wound was very effective. This method may be a valuable new technique for wound management after stoma closure.